The IDI1/SREBP2 axis drives intrahepatic cholestasis and is a treatment target of San-Huang-Cai-Zhu formula identified by sequencing and experiments - Yan, Junbin; Nie, Yunmeng; Chen, Zheng; Yao, Jiaming; Zhang, Shuo; Chen, Zhiyun (Frontiers in Pharmacology, 2023)
San-Huang-Chai-Zhu formula (SHCZF) is originated from Da-Huang-Xiao-Shi decoction (DHXSD) for the treatment of jaundice as recorded in the Chinese traditional Chinese medicine book Jin Gui Yao Lue. In the clinic, SHCZF has been used to treat cholestasis-related liver disease by improving intrahepatic cholestasis, but the treating mechanism has not been elucidated. In the study, 24 Sprague-Dawley (SD) rats were randomly assigned to the normal, AIC, SHCZF, and ursodeoxycholic Acid (UDCA) groups. 36 SD rats were divided into dynamic groups, including normal 24 h, AIC 24 h, normal 48 h, AIC 48 h, normal 72 h, and AIC 72 h. ANIT was used to induce the AIC rats model. Serum biochemical indices and hepatic pathology were detected. Part of the hepatic tissues was used to sequence, and others were used for subsequent experiments. Sequencing data combined with bioinformatics analysis were used to screen target genes and mechanisms of SHCZF in treating AIC rats. Quantitative real-time PCR (qRT-PCR) and western blotting (WB) were used to detect the RNA/Protein expression of screened genes. Rats in the dynamic group were used to determine the sequence of cholestasis and liver injury. High-performance liquid chromatography (HPLC) was used to determine the representative bio-ingredients of SHCZF. Sequencing and bioinformatics analysis suggested that IDI1/SREBP2 are hub target genes of SHCZF to ameliorate ANTI-induced intrahepatic cholestasis in rats. The treatment mechanism is associated with the regulation of lipoprotein receptor (LDLr) to reduce cholesterol intake and 3-Hydroxy-3-Methylglutaryl-CoA reductase (HMGCR), 3-Hydroxy-3-Methylglutaryl-CoA synthase 1 (HMGCS1) to decrease cholesterol synthesis. Animal experiments showed that SHCZF significantly reduced the expression of the above genes and pro-inflammatory cytokine lipocalin 2 (LCN2), inflammatory cytokines interleukin 1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α), improving intrahepatic cholestasis and inflammation and liver injury.